Awareness and uptake of the Determined, Resilient, Empowered, AIDS-free, Mentored and Safe HIV prevention package over time among population-based cohorts of young women in Kenya and South Africa. (15th June 2022) - Gourlay, Annabelle J.; Birdthistle, Isolde; Mulwa, Sarah; Mthiyane, Nondumiso T.; Magut, Faith; Chimbindi, Natsayi; Ziraba, Abdhalah; Otieno, Moses; Kwaro, Daniel; Osindo, Jane; Kamire, Vivienne; Shahmanesh, Maryam; et al.
Abstract : Objectives: To evaluate uptake of a complex intervention for HIV prevention among general populations of adolescent girls and young women (AGYW) in three diverse settings. Design: Cohorts of ∼1500 AGYW were randomly selected from demographic platforms in Kenya (Nairobi and Siaya) and South Africa (uMkhanyakude, KwaZulu-Natal). Methods: AGYW aged 13/15–22 years were enrolled in 2017 (Nairobi and uMkha-nyakude) or 2018 (Siaya), with annual follow-up to 2019. We describe awareness of DREAMS (Determined, Resilient, Empowered, AIDS-free, Mentored and Safe), self-reported invitation to participate, and uptake of DREAMS interventions by: categories and levels of the PEPFAR core package;number of 'primary' interventions (seven in Kenya;five in South Africa). Analyses were stratified by year invited and age at cohort enrolment. Results: Proportions aware and invited to DREAMS increased across all settings, to ≥ 83% aware and ≥ 53% invited by 2018 (highest among AGYW aged 13–17 years, e.g. 63 vs. 40% among 18–22 s, uMkhanyakude). HIV testing, school-based interventions and social protection were the most accessed categories, while differences in uptake by DREAMS invitation were greatest for novel DREAMS interventions, for example, social asset building (76% among those invited in 2017 and 2018 vs. 9% among those never-invited in Nairobi). Although few DREAMS invitees accessed all intended primary interventions by 2019 (2% of 15–17 s and 5% of 18–22 s in Gem), many accessed at least three interventions, including combinations across individual, family and community levels. Conclusion: Over time, DREAMS reached high proportions of AGYW in all settings, particularly younger AGYW. Participation in combinations of interventions improved but uptake of the complete primary packages remained low.